Remerciements/Acknowledgements - Thompson, Mark (Relations Industrielles / Industrial Relations, 2009)
An acknowledgement speech by Mark Thompson, Professor Emeritus, Sauder School of Business, University of British Columbia, is presented. Firstly, Thompson would like to thank Laval University and his colleagues and friends in the Department of industrial relations for this great honor, one of the great moments of his life. This honor is even more significant taking into account the major role that the Department plays in the study of industrial relations in Canada. Thompson also would like to address the graduates. They were fortunate to study various subjects in industrial relations with well-known professors. In the future, they will have many occasions to recall what they learned in their studies.
Keywords: Awards & honors; Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Labor Unions; Labor relations; University professors